2022
DOI: 10.3390/ijerph192013096
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Neuro-Feedback Training for PTSD Symptoms: A Systematic Review and Meta-Analysis

Abstract: If the negative emotions experienced in life become trauma, they affect daily life. Neuro-feedback technology has recently been introduced as a treatment, but many different neuro-feedback protocols and methods exits. This study conducted a meta-analysis of neuro-feedback training for post-traumatic stress disorder (PTSD) symptoms to evaluate the effects of functional magnetic resonance imaging (fMRI) and electroencephalogram (EEG)-based neuro-feedback training. A search of PubMed, the Cochrane Library, Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Specifically in the treatment of PTSD, training with NFBK for autoregulatory neuromodulation has been effective in improving symptoms (85).…”
Section: Cortical Patternsmentioning
confidence: 99%
“…Specifically in the treatment of PTSD, training with NFBK for autoregulatory neuromodulation has been effective in improving symptoms (85).…”
Section: Cortical Patternsmentioning
confidence: 99%
“…Prior systematic reviews and meta-analyses on randomized controlled trials (RCTs) have shown promising results using electroencephalogram (EEG) NF for PTSD but used traditional EEG NF technologies and with very small numbers of patients ( 1 ). More recent systematic reviews and meta-analyses have included duplicate studies ( 2 ) or non-randomized studies ( 2 , 3 ) or been incomplete in their systematic review of RCTs ( 4 , 5 ). Additionally, several RCTS (using newer forms of deep brain feedback—functional magnetic resonance imaging [fMRI] NF and fMRI informed EEG NF) have been published in the past 2–3 years.…”
Section: Introductionmentioning
confidence: 99%
“…In neurofeedback training, users learn to manipulate their neural activity based on direct feedback from the device. Since neurofeedback has been successfully used in treatment of impulse control problems in non-offenders ( Sokhadze et al, 2008 ; van Doren et al, 2019 ; Hong and Park, 2022 ; Lima et al, 2022 ; Moreno-García et al, 2022 ) and is thought to target neural and cognitive processes that underlie offending behaviors ( Bijlsma et al, 2022 ), it could also be a meaningful neurorehabilitation method in offender treatment ( Van Outsem, 2011 ).…”
Section: Introductionmentioning
confidence: 99%